2020
DOI: 10.1002/acs.3154
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive yaw stability control by coordination of active steering and braking with an optimized lower‐level controller

Abstract: Summary In this article, an integrated multiinput multioutput model reference adaptive control algorithm is presented based on active front steering and effective direct yaw moment distribution as an advanced driver assistance system. Vehicle parameter uncertainties in mass and tire‐road friction coefficient are considered through adaptation laws at the upper level in the control structure. The efficient distribution of yaw moment on the rear wheels is performed via a constrained optimization at the lower cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The bicycle model is used as the reference model with the following assumption, Mz*=0, μ=1, β=tan1true(vyvxtrue), Mdz=0, and Fdy=0. 23…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bicycle model is used as the reference model with the following assumption, Mz*=0, μ=1, β=tan1true(vyvxtrue), Mdz=0, and Fdy=0. 23…”
Section: System Descriptionmentioning
confidence: 99%
“…The second constraint, which indicates the physical limitation as well as the vehicle's lateral stability range for the tyre, is as follows. 23,32 …”
Section: Hierarchical Controller Designmentioning
confidence: 99%
“…However, the resulting control performance is not satisfactory. A neural network-based PI algorithm was proposed in Peng et al, 16 but the hybrid controller still showed a weak improvement compared to the pure PI controller in Wang et al 15 To further improve the control performance, some nonlinear and optimization-based controllers were employed to enhance the DYC control performance, such as linear and nonlinear model predictive control (MPC), 17 robust H control, 18 adaptive control, 19,20 etc. Zhao et al 21 released a μ controller to track desired sideslip angle and yaw rate upon a four-wheel steer-by-wire vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating and coordinating DYC and AFS is a useful approach to limit the excessive use of external yaw moment while maintaining stability [14][15][16]. To further improve the maneuvering and yaw stability of the vehicle, researchers have employed a variety of control algorithms such as sliding mode control (SMC) [17,18], fuzzy logic control [19], optimal control [20,21], model predictive control [22,23], and so on.…”
Section: Introductionmentioning
confidence: 99%